Histological and Radiographic Evaluation of Equine Bone Structure after Implantation of Castor Oil Polymer - Selim, Mariana Baroni; Nóbrega, Fernanda Silveira; Facó, Lara Lopes; Filippo Hagen, Stefano Carlo; De Zoppa, André Luís do Valle; Arana Chavez, Victor Elias; Corrêa, Luciana (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The main purpose of this study was to evaluate the characteristics of a vegetal polymeric biomaterial intended for bone substitution in horses and to investigate the responses of the equine third metacarpal bone to biomaterial implantation.Materials and Methods Six horses were submitted to osteotomy on the dorsal aspect of the left and right third metacarpal bones; one bone defect was randomly selected for treatment with biopolymer, while the other was left untreated and served as a control. Bone density was monitored radiographically after surgery and bone biopsy fragments were collected at the end of the 120-day follow-up period. Biopsy fragments were analysed using light and scanning electron microscopy.Results Mean bone density values (mmAL) were greater in control defects (16.33 ± 1.6) than in polymer-treated defects (14.17 ± 1.7) at 120 days (p = 0.027). Light microscopy revealed greater percentages of new bone formation in control defects (50.15 ± 14.8) than in polymer treated defects (26.94 ± 12.1) at 120 days (p < 0.0001). Scanning electron microscopy analysis suggested a similar quality of pre-existing bone and new bone formed in the presence of biomaterial.Clinical Significance The absence of adverse reactions supports biomaterial biocompatibility and osteoconducting capacity and suggests the castor oil polymer is a suitable bone substitute for the treatment of bone defects in horses.
Keywords: horse; bone substitute; bone densitometry; castor oil polymer; microscopy